The Oxford dictionary of architecture - Curl, James Stevens 1937-; Wilson, Susan (New York Oxford University Press, 2015)
Covers all periods of western architectural history including biographies of architects and others who have made significant contributions to the field of architecture.
Includes bibliographical references.
Keywords: Architecture -- Dictionaries; Landscape architecture -- Dictionaries